2012
DOI: 10.1002/ijc.27982
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of prolyl‐4‐hydroxylase domain 2 inhibits tumor growth of human breast cancer MDA‐MB‐231 cells by affecting TGF‐β1 processing

Abstract: The prolyl-4-hydroxylase domain 1-3 (PHD1-3) enzymes are regulating the protein stability of the a-subunit of the hypoxiainducible factor-1 (HIF-1), which mediates oxygen-dependent gene expression. PHD2 is the main isoform regulating HIF-1a hydroxylation and thus stability in normoxia. In human cancers, HIF-1a is overexpressed as a result of intratumoral hypoxia which in turn promotes tumor progression. The role of PHD2 for tumor progression is in contrast far from being thoroughly understood. Therefore, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
(57 reference statements)
3
26
0
Order By: Relevance
“…efficiency of EGFR mRNA [16] or via the attenuation of rabaptin-5 transcription, which leads to longer halflives of activated EGFR due to delayed late endosomal EGFR sorting [33]. Therefore, we initially expected that the knockdown of PHD2 and, as shown previously [28], the stabilization of HIF-1α and HIF-2α in our cell model (Supplementary Figure 2) would favor the upregulation of EGFR. However, the experimental results were quite opposite.…”
Section: Discussionmentioning
confidence: 71%
“…efficiency of EGFR mRNA [16] or via the attenuation of rabaptin-5 transcription, which leads to longer halflives of activated EGFR due to delayed late endosomal EGFR sorting [33]. Therefore, we initially expected that the knockdown of PHD2 and, as shown previously [28], the stabilization of HIF-1α and HIF-2α in our cell model (Supplementary Figure 2) would favor the upregulation of EGFR. However, the experimental results were quite opposite.…”
Section: Discussionmentioning
confidence: 71%
“…Silencing of PHD2 in BC cells reduces TGF-b1 secretion (Wottawa et al, 2013). In agreement, PHD2 haplodeficient PyMT cancer cells released less TGF-b1.…”
Section: Phd2-dependent Regulation Of Tgf-b1 Crosstalkmentioning
confidence: 84%
“…Selective PHD2 haplodeficiency in ECs reduces metastasis without affecting tumor growth by normalizing tumor vessels (Leite de Oliveira et al, 2012;Mazzone et al, 2009), while deficiency of PHD2 in immune cells decreases tumor growth (Mamlouk et al, 2014). However, others reported that PHD2 silencing in cancer cells increases or decreases tumor growth via different underlying mechanisms (Klotzsche-von Ameln et al, 2011;Bordoli et al, 2011;Chan et al, 2009;Su et al, 2012;Wottawa et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike HIFα, the role of PHDs in tumorigenesis remains poorly understood. PHDs can function as tumor suppressors as well as tumor oncogenes depending on the cancer context (Bordoli et al, 2011;Erez et al, 2003;Heindryckx et al, 2012;Jokilehto and Jaakkola, 2010;Kato et al, 2006;Klotzschevon Ameln et al, 2012;Klotzsche-von Ameln et al, 2011;Lee et al, 2008;Lee et al, 2005;Mamlouk et al, 2014;Su et al, 2012;Wottawa et al, 2013;Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 97%